Incidencia de las estrategias metodológicas en el desarrollo del Atletismo en los Estudiantes del 8vo año de Educación Básica del Colegio Nacional Republica del Ecuador de la Ciudad de Machala, sector los Vergeles durante el periodo lectivo 2012-2013. - Figueroa Vélez, Julio César (2014)
Athletics is a sport so it is important to perform an adequate job , and planned with the students of the 8th year of basic general education so I introduced the topic of the thesis entitled Impact of methodological strategies in the development of Athletics in 8th grade students of Basic Education of the Republic of Ecuador National College of the City of Machala, orchards industry during the 2012-2013 school period , the same is divided into five chapters.